Feet of death [videorecording (DVD)] - Chick, James; Chick, Ashley; Stahl, Ryan; Brown, Andrew Jacob; Vanover, Jack; Watts, Benjamin (Indie Rights, 2025)
When paranormal social media influencer, Chris Dixon, winds up dead near the base of Mt. Saint Helens, Jason Esterly, a USFS ranger, must pull himself out of mourning his late wife to grapple with the reality that Bigfoot could actually exist. The supposed mythical creature might even be responsible for a string of unusual deaths in his small town.